Induction of tomato resistance against Corynespora leaf spot from Trichoderma spp. and degrading enzymes activities - Saepisan, Suwita; Saksirirat, Weerasak; Huehne, Pattana Srifah (Asia-Pacific Journal of Science and Technology, 2017)
Thirty ve isolates of Trichoderma spp. were tested on induce resistance to Corynespora leaf spot in tomato. The high potential induce resistance was Trichoderma isolate T24 showing lowest number of spot 41.0 spots followed by isolates T17 and 88 with number of spots 43.3 and 55.7, respectively. All 35 isolates were also evaluated on their ability to induce degrading enzymes in tomato leaves, which showed that tomato inoculated with Trichoderma isolate 162 expressed high chitinase activity of 857.2 μmol (GlcNAc equivalent)/mg protein/hr, isolates T18 and T13 showed activities of 763.7 and 750.6 μmol (GlcNAc equivalent)/mg protein/hr, respectively. For protease activity, tomato inoculated with Trichoderma isolates 85, 67 and 115 showed activity of 850.3, 778.0 and 775.5 μmol (tyrosine equivalent)/mg protein/hr, respectively. Hight activities of b-1,3-glucanase were obtained from tomato inoculated with Trichoderma isolates T4, 103 and 106 with 498.6, 471.1 and 466.4 μmol (glucose equivalent)/mg protein/hr, respectively. This result is to applied for isolate selection of Trichoderma for further chitinase gene transformation.